Questing abundance of adult taiga ticks Ixodes persulcatus and their Borrelia prevalence at the north-western part of their distribution - Pakanen VM; Sormunen JJ; Sippola E; Blomqvist D; Kallio ER (BMC, 2022)
BackgroundBecause ixodid ticks are vectors of zoonotic pathogens, including Borrelia, information of their abundance, seasonal variation in questing behaviour and pathogen prevalence is important for human health. As ticks are invading new areas northwards, information from these new areas are needed. Taiga tick (Ixodes persulcatus) populations have been recently found at Bothnian Bay, Finland. We assessed seasonal variation in questing abundance of ticks and their pathogen prevalence in coastal deciduous forests near the city of Oulu (latitudes 64-65 degrees) in 2019.MethodsWe sampled ticks from May until September by cloth dragging 100 meters once a month at eight study sites. We calculated a density index (individuals/100 m(2)) to assess seasonal variation. Samples were screened for Borrelia burgdorferi (sensu lato) (including B. afzelii, B. garinii, B. burgdorferi (sensu stricto) and B. valaisana), Borrelia miyamotoi, Anaplasma phagocytophilum, Rickettsia spp., Neoehrlichia mikurensis, Francisella tularensis and Bartonella spp., Babesia spp. and for the tick-borne encephalitis virus.ResultsAll except one nymph were identified as I. persulcatus. The number of questing adults showed a strong peak in May (median: 6.5 adults/100 m(2)), which is among the highest values reported in northern Europe, and potentially indicates a large population size. After May, the number of questing adults declined steadily with few adults still sampled in August. Nymphs were present from May until September. We found a striking prevalence of Borrelia spp. in adults (62%) and nymphs (40%), with B. garinii (51%) and B. afzelii (63%) being the most common species. In addition, we found that 26% of infected adults were coinfected with at least two Borrelia genospecies, mainly B. garinii and B. afzelii, which are associated with different host species.ConclusionsThe coastal forest environments at Bothnian Bay seem to provide favourable environments for I. persulcatus and the spread of Borrelia. High tick abundance, a low diversity of the host community and similar host use among larvae and nymphs likely explain the high Borrelia prevalence and coinfection rate. Research on the infestation of the hosts that quantifies the temporal dynamics of immature life stages would reveal important aspects of pathogen circulation in these tick populations.